The Social Psychology of Morality: Exploring the Causes of Good and Evil. 2012
DOI: 10.1037/13091-008
|View full text |Cite
|
Sign up to set email alerts
|

Honest rationales for dishonest behavior.

Abstract: Cheating, fraud, racketeering, and other forms of dishonesty are among the greatest personal and societal challenges of our time. While the media commonly highlight extreme examples and focus on the most sensational scams (e.g., those by Enron and Bernard Madoff), less exposure is given to the prevalence of "ordinary" unethical behavior-dishonest acts committed by people who value morality but act immorally when they have an opportunity to cheat. Examples include cheating on one's taxes and engaging in "wardro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 70 publications
4
70
0
Order By: Relevance
“…Justifications offer another way to solve ethical inconsistencies (Ayal & Gino, 2011;Gino & Ariely, 2012). People may justify their actions by reference to norms (-everyone is doing it‖), to external pressures (-if I do not do it, I'll be fired‖), or to altruism and a greater cause (-this is what it takes to ensure people do not lose their jobs‖) (e.g., Gino & Pierce, 2009;Sachdeva, Iliev, & Medin, 2009;Kulik, Sledge, & Mahler, 1986).…”
Section: Solving Ethical Inconsistenciesmentioning
confidence: 99%
“…Justifications offer another way to solve ethical inconsistencies (Ayal & Gino, 2011;Gino & Ariely, 2012). People may justify their actions by reference to norms (-everyone is doing it‖), to external pressures (-if I do not do it, I'll be fired‖), or to altruism and a greater cause (-this is what it takes to ensure people do not lose their jobs‖) (e.g., Gino & Pierce, 2009;Sachdeva, Iliev, & Medin, 2009;Kulik, Sledge, & Mahler, 1986).…”
Section: Solving Ethical Inconsistenciesmentioning
confidence: 99%
“…Defined as a compensatory process used when one’s moral self-concept has been threatened (Sachdeva et al, 2009), moral cleansing is an act that reaffirms one’s core values and beliefs, resulting in the restoration of one’s moral self-image as well as the reduction of the tension experienced (Ayal & Gino, 2012) after engaging in (Steele, 1988) or merely contemplating (Tetlock, 2003) immoral acts. For example, Carlsmith and Gross (1969) found that participants were significantly more likely to help another person after engaging in the immoral act of shocking a confederate compared to only watching someone shock a confederate or providing a confederate with negative feedback.…”
Section: Moral Cleansingmentioning
confidence: 99%
“…Not only can cheating result in negative consequences for oneself and others (Ayal & Gino, 2012), but it can also threaten a person’s moral identity, or a person’s belief that “certain moral traits are essential to his or her self-concept” (Aquino & Reed, 2002, p. 1425) and that he or she is in fact a moral person, identifying with higher-order values (Sachdeva, Iliev, & Medin, 2009). Because people strive to maintain positive self-concepts (Greenwald, 1980), mechanisms such as moral cleansing , a process in which people reaffirm their moral values (e.g., by contemplating moral acts), are used to maintain a moral self-image despite sometimes thinking about or actually engaging in immoral acts (Tetlock, Kristel, Elson, Lerner, & Green, 2000).…”
mentioning
confidence: 99%
“…However, if an individual does not possess a capacity for experiencing the affiliative, prosocial emotions to accompany or guide his or her actions, having only an explicit knowledge of moral norms may be insufficient to motivate moral behavior (Moll, De Oliviera-Souza, and Zahn 2008). To the degree that typical individuals engage in typical immoral acts (e.g., lying, cheating), they also appear to engage in compensatory behaviors to undo the psychological and emotional tension-the "ethical dissonance" created by having performed a deed inconsistent with one's self-perception of being a moral agent (Ayal and Gino 2012). This reduction in tension is accomplished via altruistic reparation, confession, symbolic purification, or comparing one's behavior with the behaviors of others (Ayal and Gino 2012).…”
mentioning
confidence: 97%
“…To the degree that typical individuals engage in typical immoral acts (e.g., lying, cheating), they also appear to engage in compensatory behaviors to undo the psychological and emotional tension-the "ethical dissonance" created by having performed a deed inconsistent with one's self-perception of being a moral agent (Ayal and Gino 2012). This reduction in tension is accomplished via altruistic reparation, confession, symbolic purification, or comparing one's behavior with the behaviors of others (Ayal and Gino 2012). Individuals who make severe and persistent moral violations, on the other hand, may be primarily driven by a deficient or disturbed capacity for experiencing the necessary emotions that underlie attachment to the social world.…”
mentioning
confidence: 98%